Lying in Bed: An Analysis of Deceptive Affectionate Messages During Sexual Activity in Young Adults' Romantic Relationships. Issue 2 (15th March 2019) - Bennett, Margaret; Denes, Amanda
Abstract : Guided by affection exchange theory, the present study examined the associations among deceptive affectionate messages (DAMs) during sexual activity and duration of post-sex affectionate behavior, sexual satisfaction, and relationship satisfaction. Two-hundred twenty-eight participants ages 18–30, the majority of whom identified as White, completed a survey assessing deceptive and sexual communication. Linear regression and serial mediation using sexual satisfaction and post-sex affectionate behavior as sequential mediators revealed that more DAMs are associated with less sexual satisfaction, less post-sex communication, and less relationship satisfaction. The findings provide a more complete picture of how DAMs affect sexual encounters and may be used to inform interventions aimed at promoting healthier sexual relationships. Additionally, the implications for affection exchange theory are discussed.